Partners jockey for position. (to become preferred providers of complementary software for Microsoft Exchange Server)(Intranet Applications) - McNaamara, Paul (Network world, 1998)
A growing number of independent software vendors are scrambling to provide complementary software now that more than 10 million customers are accessing machines running Microsoft Exchange Server. Microsoft insists that a level playing field exists for all Exchange partners and urges customers to be wary of claims to the contrary. However, Microsoft's purported stamp of approval has become the subject of debate among some partners, particularly those in the workflow applications market.